The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s0263574721000175
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Configuration and Innovation Control System Design for Power Cable Line Mobile Maintenance Robot – ADDENDUM

Abstract: In the above article an affiliation for Wei Jiang was omitted, Wei Jiang's second affiliation is as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…For four split high-voltage transmission lines, Hong Jun Li et al designed a drainage plate maintenance robot and suggested a reliable trajectory tracking motion control approach using sliding mode variable structure control theory [22]. In order to repair insulator strings, spacers, maintain dampers, and replace drainage plates, Jiang Wei et al studied the power maintenance robot [23]. By using kinematics modeling and analysis of the working area based on the Monte Carlo approach, the mechanical structure of the robot was optimized.…”
Section: Introductionmentioning
confidence: 99%
“…For four split high-voltage transmission lines, Hong Jun Li et al designed a drainage plate maintenance robot and suggested a reliable trajectory tracking motion control approach using sliding mode variable structure control theory [22]. In order to repair insulator strings, spacers, maintain dampers, and replace drainage plates, Jiang Wei et al studied the power maintenance robot [23]. By using kinematics modeling and analysis of the working area based on the Monte Carlo approach, the mechanical structure of the robot was optimized.…”
Section: Introductionmentioning
confidence: 99%